The Learning of Liberty The Educational Ideas of the American Founders - Pangle, Thomas L. (University Press of Kansas, 1993)
American schools are in a state of crisis.At the root of our current perplexity, beneath the difficulties with funding, social problems, and low test scores, festers a serious uncertainty as to what the focus and goals of education should be. We are increasingly haunted by the suspicion that our educational theories and institutions have lost sight of the need to perpetuate a core of moral and civic knowledge that is essential for any citizen's education, and indeed for any individual's happiness. Mining the Founders' rich reflections on education, the Pangles suggest, can help us recover a clearer sense of perspective and purpose.With a commanding knowledge of the history of political philosophy, the authors illustrate how the Founders both drew upon and transformed the ideas of earlier philosophers of education such as Plato, Xenophon, Milton, Bacon, and Locke. They trace the emergence of a new American ideal of public education that puts civic instruction at its core to sustain a high quality of leadership and public discourse while producing resourceful, selfreliant members of a uniquely fluid society. The Pangles also explore the wisdom and the weaknesses inherent in Jefferson's attempt to create a comprehensive system of schooling that would educate parents and children and offer unprecedented freedom of choice to university students. An original closing section examines the Founders' ideas for bringing all aspects of society to bear on education. It also shows how Washington, Jefferson, and Franklin presented their own lives as models for the education of others and analyzes the subtle, provocative moral philosophy implicit in the selfdepiction of each.The Learning of Liberty is historical and scholarly yet relentlessly practical, seeking from the Founders useful insights into the human soul and the character of good education. Even if the Founders do not provide us with readymade solutions to many of our problems, the Pangles suggest, a study of their writings can give us a more realistic perspective, by teaching that our bewilderment is in some measure an outgrowth of unresolved tensions embedded in the Founders' own conceptions of republicanism, religion, education, and human nature.